Leadership Transformation and Organizational Strengthening in Improving Collaboration and Operational Effectiveness of Islamic Boarding Schools - Hikmatul Hidayah; Febriyanti Ghayatul Qushwa; Izzatul Munawwaroh; Dinda Febrianti Putri; Rizkiyah Hasanah (Journal of Social Studies and Education, 2024)
This study examines the role of leadership initiatives and organizational strengthening in Nurul Jadid and Zainul Hasan Islamic Boarding Schools in increasing operational effectiveness and adaptation to changing times. The main focus of this research is to understand how pesantren leaders identify opportunities and challenges, as well as design innovative solutions to deal with social dynamics and educational needs. The research method used is a qualitative approach with a case study design, which involves in-depth interviews, observations, and documentation analysis. Information sources were obtained from the head of the pesantren, management staff, and several members of the managerial team who were directly involved in the implementation of programs and policies. Data analysis techniques are carried out through data reduction, data display, and verification to obtain valid and relevant findings. The results of the study show that leadership initiatives, such as the application of technology in administration and inclusive-based education programs, contribute significantly to improving operational efficiency and collaboration between units in both Islamic boarding schools. Strengthening the organization through restructuring and regular training has also proven effective in increasing transparency and accountability. The implications of this study are the importance of proactive and collaborative leadership in creating organizations that are adaptive to change, as well as how pesantren can utilize technological innovations to improve operational performance without neglecting traditional values.